IDENTIFIKASI KONSISTENSI ILMIAH SISWA DALAM MENYELESAIKAN MASALAH TUMBUKAN DENGAN MENGGUNAKAN TES MULTIREPRESENTASI - Wijana, Made; Pasaribu, Marungkil; Darmadi, I Wayan (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
Students' consistency can increase when they gain more experience in learning physics. Multi-representation is a representation of a concept that is done using many ways. Giving multi-representation tests to students can be used to determine the level of consistency of students to a concept in different contexts. This study was a qualitative descriptive study aimed to identifying the level of scientific consistency of students in solving collision problems using multirepresentation tests. The research subjects were students of SMA Negeri 3 Palu, garde 11th MIA 7 for the 2018/2019 academic year which consisted of 27 students who took part in the consistency test and 3 students were selected in the interview activities according to the respondent's category. The research instrument consisted of 21 multiple choice questions with different forms of representation which were divided into 4 themes. The results showed that the level of scientific consistency of students in solving collision problems was generally at level 3 or inconsistent which indicated that students' understanding of concepts in collision material was still low.